NUTRITION NUTRITIONS FOR CHILDREN AND ADOLESCENTS - S. Ermatova (Galaxy International Interdisciplinary Research Journal, 2022)
Adequate nutrition is important for a school student in terms of quantity and quality. Inadequate nutrition and poor quality of food have the same negative impact on children's physical and mental development. They need a complete set of nutrients: proteins, fats, carbohydrates, minerals and vitamins.